Antimicrobial, anti-inflammatory and antioxidant activity of Nigella sativa in clinically endometritic cows - Yildiz, Atilla; Balikci, Engin (Taylor & Francis Ltd, 2016)
The aim of this study was to investigate the response to intrauterine infusion of Nigella sativa (NS) and ceftiofur and to evaluate the possible antimicrobial, antioxidant and anti-inflammatory effects of NS in clinically endometritic cows. A total of 30 clinically endometritic cows (10 cows in each group) were randomly divided into 3 treatment groups: an i.u. infusion of 100mL of methanol extract of NS was given once a day during 3 days in group NS; an i.u. infusion of a 20-mL suspension (Excenel (R), Pfizer) containing 1g of ceftiofur as ceftiofur hydrochloride was given once a day during three days in group CH; cows with no treatment belonged to group C.After the treatment, there were slight vaginal discharges in 3/10 animals in group NS and 2/10 animals in group CH. GSH-Px and superoxide dismutase levels increased and malondialdehyde concentration decreased significantly (P<.05) in groups NS and CH after treatment when compared to pretreatment ones. Hp and SAA levels of groups NS and CH decreased significantly (P<.05) after treatment when compared to group C.NS had antimicrobial, antioxidant and antiinflamatory effects in clinical endometric cows. Although the antimicrobial effect of NS was less than that of CH, this study indicates a therapeutic value of NS in clinically endometritic cows. NS might be a promising therapy for cows with clinical endometritis in the future.
Keywords: Nigella sativa; antimicrobial; antioxidant; antiinflamatory; endometritic cows